Microbiologically induced concrete corrosion: A case study from a combined sewer network. (November 2015) - Grengg, C.; Mittermayr, F.; Baldermann, A.; Böttcher, M.E.; Leis, A.; Koraimann, G.; Grunert, P.; Dietzel, M.
Abstract: In this study, a strongly deteriorated concrete-based sewer system was investigated by using a multi proxy approach based on gaseous, hydro-geochemical, microbiological, mineralogical and mechanical analyses. Therefore, gas, liquid, and solid samples were taken throughout the entire sewer system. Long term measurements of gaseous hydrogen sulfide (H2 S) within the sewer atmosphere yielded concentrations up to 367 ppm. Interstitial fluids, extracted from deteriorated concrete by squeezing, contained sulfate (SO4 2 − ) concentrations of up to 104 g l − 1 at strong acidic conditions (0.7 > pH > 3.1) and are close to the saturation state of gypsum. This sulfuric acid attack is indicative for a well-established biofilm containing sulfide oxidizing bacteria (SOB), which was analyzed to consist mainly of Acidithiobacillus thiooxidans . The micro-structure of the attacked concrete displays a progressing alteration zone, which is caused by microbially induced concrete corrosion (MICC), with a suggested pH gradient from about 13 to < 1, from the intact inner concrete zone to the outermost heavily deteriorated concrete. Calcium sulfate minerals such as gypsum (CaSO4 · 2H2 O), bassanite (CaSO4 · 1/2H2 O) and anhydrite (CaSO4 ) are abundant in the altered concrete, which were formed from the dissolution of the cement phases and Ca-bearing aggregates. Remarkably high corrosion rates of different precast concrete manholes were quantified to reach values greater than 1 cm yr − 1, despite the fact that C3 A-free cement, fly ash and a w/c of 0.35 was used.